Magnesium Thixomolding Injection Molding Material
Patent Information
- Application Number
- JP2020050632
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-23
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-03-23
Smart Images

Figure 0007639272000001 
Figure 0007639272000002 
Figure 0007639272000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to magnesium thixomolding injection molding materials. [Background technology]
[0002] In recent years, magnesium alloy parts have been used in products such as automobiles, aircraft, mobile phones, and laptops. Magnesium has a higher specific strength than iron, aluminum, etc., so parts made from magnesium alloys can be lightweight and strong. In addition, magnesium is abundant near the earth's surface, so it has the advantage of being easily available as a resource.
[0003] Thixomolding is known as one of the methods for manufacturing magnesium parts. In thixomolding, the material is made more fluid by heating and shearing before being injected into a mold, making it possible to mold thinner parts and parts with complex shapes compared to die casting. In addition, since the material is injected into the mold without coming into contact with the air, there is no need to worry about the SF 6 Another advantage is that the molded product can be molded without using any flame retardant gas such as benzene.
[0004] Materials used for thixomolding include chips, pellets, powder, etc. For example, Patent Document 1 discloses magnesium-based alloy powder used as a material for thixomolding. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-44227 A Summary of the Invention [Problem to be solved by the invention]
[0006] Patent Document 1 indicates that molded products made from the above-mentioned materials have high strength. However, the present inventors have found that when thixomolding is performed using a powdered magnesium material as shown in Patent Document 1, there is a possibility that the strength of the molded products may vary. [Means for solving the problem]
[0007] According to a first aspect of the present disclosure, there is provided a magnesium thixomolding injection molding material. The magnesium thixomolding injection molding material includes a powder containing Mg as a main component and chips containing Mg as a main component. The ratio of the powder in the magnesium thixomolding injection molding material is 5% by mass or more and 45% by mass or less, and the tap density of the powder is 0.15 g / cm. 3 That's all. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram showing an example of a configuration of an injection molding machine. [Diagram 2] FIG. 2 is a process diagram showing an example of a method for producing a mixed material. [Diagram 3] FIG. 2 is a process diagram showing an example of a method for producing a molded product. [Figure 4] FIG. 13 is a diagram showing experimental results. [Diagram 5] FIG. 13 is a diagram showing experimental results. [Figure 6] FIG. 2 is a cross-sectional view of a cavity of a mold used to mold each sample. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] A. Embodiment: FIG. 1 is a schematic diagram showing an example of the configuration of an injection molding machine 1 used in thixomolding. Thixomolding is a method of forming a slurry of materials such as chips and powder by heating and shearing, and injecting the slurry without exposing it to the air to obtain a molded product of a desired shape. In thixomolding, a molded product is generally formed at a lower temperature than in a die casting method, etc., and the structure of the molded product is easily homogenized. Therefore, by molding a molded product by thixomolding, the mechanical strength and dimensional accuracy of the molded product can be improved. In this specification, the term "molded product" simply refers to a product molded by thixomolding.
[0010] The molded articles produced by thixomolding are used for components constituting various products, etc. The molded articles are used for, for example, transportation equipment parts such as automobile parts, railway vehicle parts, ship parts, and aircraft parts, electronic equipment parts such as personal computer parts, mobile phone terminal parts, smartphone parts, tablet terminal parts, wearable device parts, and camera parts, as well as various structures such as ornaments, artificial bones, and artificial dental roots.
[0011] As shown in FIG. 1, the injection molding machine 1 includes a mold 2 that forms a cavity Cv, a hopper 5, a heating cylinder 7 having a heater 6, a screw 8, and a nozzle 9. When thixomolding is performed by the injection molding machine 1, first, a material is charged into the hopper 5. The charged material is then supplied from the hopper 5 to the heating cylinder 7. The material supplied to the heating cylinder 7 is heated in the heating cylinder 7 by the heater 6, and is sheared while being transported by the screw 8 to form a slurry. The slurry is injected into the cavity Cv in the mold 2 through the nozzle 9 without coming into contact with the air.
[0012] The magnesium thixomolding injection molding material of this embodiment includes a powder containing magnesium (Mg) as a main component and chips containing Mg as a main component. The ratio of the powder in the magnesium thixomolding injection molding material is 5% by mass or more and 45% by mass or less. The tap density of the powder is 0.15 g / cm 3 That's it. The main component refers to the substance that is contained in the powder or chips at the highest concentration. Magnesium thixomolding injection molding material is sometimes simply called the "mixed material."
[0013] Chips are pieces obtained by cutting or cutting Mg alloys cast in a mold. Chips may have other compositions or shapes as long as they are mainly composed of Mg. Chips are also sometimes called pellets.
[0014] The powder refers to metal particles of Mg alloy having a substantially spherical or flaky shape. The powder is preferably produced by an atomization method, and more preferably by a high-speed rotating water flow atomization method. In addition to the high-speed rotating water flow atomization method, examples of the atomization method include a water atomization method and a gas atomization method. The powder may also be produced by a method other than the atomization method, such as a reduction method or a carbonyl method.
[0015] In the high-speed rotating water flow atomization method, first, a cooling liquid is jetted along the inner peripheral surface of a cooling cylinder, and then rotated along the inner peripheral surface of the cooling cylinder to form a cooling liquid layer on the inner peripheral surface. Furthermore, the raw material of the Mg alloy is melted, and the resulting molten metal is allowed to fall naturally while a liquid or gas jet is sprayed onto it. This causes the molten metal to scatter and become finer, and is blown into the cooling liquid layer and taken into the cooling liquid layer. As a result, the molten metal that has been scattered and made finer is rapidly cooled and solidified, and Mg alloy powder is obtained. In the high-speed rotating water flow atomization method, the raw material in the molten state is rapidly cooled in a short time, so that the crystal structure of the material is made finer. As a result, a powder that can be molded into a molded product with excellent mechanical properties is obtained.
[0016] The pressure of the cooling liquid supplied to the cooling cylinder when it is ejected is preferably 50 MPa or more and 200 MPa or less. Also, the temperature of the cooling liquid is preferably -10° C. or more and 40° C. or less. This allows the scattered molten metal to be cooled appropriately and evenly in the cooling liquid layer.
[0017] The melting temperature for melting the raw material of the Mg alloy is preferably set to a temperature between Tm+20° C. and Tm+200° C., more preferably between Tm+50° C. and Tm+150° C., relative to the melting point Tm of the Mg alloy. This makes it possible to particularly reduce the variation in properties between particles constituting the Mg alloy powder.
[0018] In the high-speed rotational water jet atomization method, by adjusting various conditions, for example, the particle size, tap density, average DAS, etc. of the produced Mg alloy powder can be adjusted. "Average DAS" refers to the average dendrite secondary arm spacing. For example, the average DAS can be reduced by increasing the flow rate or volume of the coolant. In addition, by adjusting the flow rate of the molten metal, the flow rate of the liquid or gas jet, or the flow rate or volume of the coolant, the particle size, shape, oxide layer thickness, and tap density of the Mg alloy powder can be adjusted.
[0019] In the high-speed rotating water flow atomization method, the molten metal may be made to reach the cooling layer directly without using a liquid or gas jet. In this case, for example, the cooling housing is arranged at an angle to the direction of natural fall of the molten metal. As a result, the molten metal reaches the cooling liquid layer by natural fall and is taken into the cooling liquid layer. In such a configuration, the molten metal is atomized by the flow of the cooling liquid layer and is cooled and solidified, and Mg alloy powder having a relatively large particle size is obtained.
[0020] Powder has a finer structure and less component segregation than chips, so the strength of the molded product can be increased by using a powdered material in thixomolding. On the other hand, if a material composed only of a powdered material is used in thixomolding, there is a possibility that the strength of the molded product will vary. The variation in strength of the molded product is caused, for example, by the presence or absence of air bubbles in the molded product. Air bubbles in the molded product are caused, for example, by air being entrained when the material is injected into a mold. The screws of commercially available thixomolding machines have a shape suitable for use with chips as the material, so this air entrainment is likely to occur when powder is used as the material. In particular, when the tap density of the powder is 0.15 g / cm 3 If the density is less than 100%, the powder is more likely to entrap air when injected into a mold. Air bubbles in a molded product are also called "voids".
[0021] The mixed material of this embodiment is composed of chips and powder mixed in the above-mentioned ratio. The tap density of the powder constituting the mixed material is 0.15 g / cm 3 That is all. Therefore, by using this mixed material as a material for thixomolding, the variation in strength of the molded product is suppressed compared to when a material composed of only powder material is used. Furthermore, the strength of the molded product is improved compared to when a material composed of only chips is used.
[0022] It is preferable that the powder contains calcium (Ca) as an additive component in addition to the main component Mg. The inclusion of Ca in the powder increases the ignition temperature of the powder. The increase in the ignition temperature of the powder or chips makes it easier to process the mixed material more safely and efficiently. Furthermore, it is more preferable that the content of Ca in the powder is 0.2 mass% or more. The content of Ca in the powder is 0.2 mass% or more, so that the ignition temperature of the powder increases and the strength of the molded product becomes higher. For example, the chips may contain Ca. For example, Ca may exist in the powder or chips in the form of a simple substance, an oxide, an intermetallic compound, or the like. For example, Ca may be segregated at the grain boundaries in the metal structure of Mg or Mg alloy, or may be uniformly dispersed in the powder.
[0023] The powder and chips may contain, for example, aluminum (Al) as an additive component. The addition of Al to the powder reduces the melting point of the powder. Similarly, the addition of Al to the chips reduces the melting point of the chips. The reduced melting point of the powder or chips makes the mixed material easier to process safely and efficiently. For example, Al may exist in the form of a simple substance, an oxide, an intermetallic compound, or the like in the powder or chips. Also, for example, Al may be segregated at the grain boundaries in the metal structure of Mg or Mg alloy, or may be uniformly dispersed in the powder or chips. Furthermore, the powder and chips may contain other components other than the above-mentioned Mg, Ca, and Al.
[0024] The content of additive components such as Ca in the powder or chips can be measured by, for example, electron probe microanalysis (EPMA). The content of additive components may also be measured by, for example, spark discharge optical emission spectroscopy (OES), X-ray photoelectron spectroscopy (XPS), secondary ion mass spectrometry (SIMS), Auger electron spectroscopy (AES), Rutherford backscattering spectrometry (RBS), etc.
[0025] The tap density of a powder can be measured according to JIS standard Z2512. Specifically, a sample weighed to the nearest 0.1 g is placed on a 100 cm3 The sample is placed in a measuring container of 25 cm2 and the measuring container is attached to the tapping device. Then, tapping is performed and the volume of the sample is read from the scale on the measuring container. The tap density is calculated by dividing the mass of the sample by the volume of the sample. The measuring container is 25 cm2 as specified in JIS standard Z2512. 3 The measurement container may be a measurement container having a thickness of 100 mm or less.
[0026] 2 is a process diagram showing an example of a method for producing a mixed material according to the present embodiment. As described above, the mixed material is produced by mixing chips and powder.
[0027] First, in step S110, chips and powder are prepared. Next, in step S120, the chips and powder are mixed. In step S120, for example, the chips and powder are placed in a 1-liter container with a lid and shaken. This produces a mixed material.
[0028] Fig. 3 is a process diagram showing an example of a method for producing a molded product by thixomolding using a mixed material. To produce a molded product, first, in step S210, a mixed material produced by the production method shown in Fig. 2 is prepared. Next, in step S220, molding is performed by thixomolding. In this way, a molded product is produced using the mixed material.
[0029] The temperature of the slurry in thixomolding is set appropriately depending on the composition of the material, the shape of the cavity Cv, and the like. In this embodiment, the temperature of the slurry is preferably set to 500° C. or more and 650° C. or less, and more preferably set to 550° C. or more and 630° C. or less. By setting the temperature of the slurry within the above range, the viscosity of the slurry becomes appropriate. This improves the dimensional accuracy of the molded product.
[0030] In the manufacturing method of the molded product in this embodiment, a mixed material in which powder and chips are mixed in advance is fed into the hopper 5 of the injection molding machine 1 shown in FIG. 1. Therefore, compared with the case in which powder and chips are separately fed into the injection molding machine 1 as materials, the material is uniformly dispersed in the heating cylinder 7, and the state of the slurry injected into the mold 2 is stabilized. This stabilizes the strength of the molded product to be manufactured. For example, the mixed material may be manufactured just before being fed into the injection molding machine 1. In this case, for example, a mixing mechanism may be provided in the hopper 5, so that a mixed material equivalent to the mixed material mixed in advance is manufactured in the hopper 5, and the mixed material manufactured in the hopper 5 is fed into the injection molding machine 1.
[0031] According to the mixed material of the present embodiment described above, the ratio of powder in the mixed material is 5 mass % or more and 45 mass % or less, and the tap density of the powder is 0.15 g / cm 3 As a result, the variation in strength of the molded product is suppressed compared to when thixomolding is performed using a material composed only of powder material. Furthermore, the strength of the molded product is improved compared to when thixomolding is performed using a material composed only of chips.
[0032] In addition, in this embodiment, the powder contains Ca, which increases the ignition temperature of the powder and makes the mixed material easier to process safely and efficiently.
[0033] In this embodiment, the powder contains 0.2 mass % or more of Ca, which increases the ignition temperature of the powder and increases the strength of the molded product.
[0034] B. Experimental results: Various mixed materials were prepared as experimental samples, and a proof stress test was carried out on a molded article made using the mixed materials to verify the effects of the above embodiment.
[0035] Figures 4 and 5 are diagrams showing the experimental results. Figures 4 and 5 show the powder composition, powder ratio, whether the tap density of the powder was adjusted, the tap density of the powder, the average value of the yield strength, and the difference between the average value and the minimum value of the yield strength for each sample. The yield strength in Figures 4 and 5 refers to the 0.2% yield strength of the molded product molded using each sample. The yield strength was measured by a three-point bending test.
[0036] Each sample was manufactured according to the manufacturing method shown in Fig. 2. First, chips and powder were prepared according to step S110. The chips used were AZ91D chips measuring 4 mm x 2 mm x 2 mm manufactured by STU Co., Ltd. This chip is an Mg alloy chip containing 9 mass percent Al and 1 mass percent Zn.
[0037] The powder was prepared as follows. First, the raw material was melted in a high-frequency induction furnace and pulverized by a high-speed rotating water jet atomization method to obtain Mg alloy powder. The ejection pressure of the cooling liquid was 100 MPa. The temperature of the cooling liquid was 30°C. The temperature of the molten metal was the melting point of the raw material + 20°C.
[0038] In this experiment, powders having compositions A, B, C, and D were prepared. "Composition A" means that the Al content in the powder is 9.5 mass% and the Ca content is 0.25 mass%. "Composition B" means that the Al content in the powder is 7.8 mass% and the Ca content is 0.25 mass%. "Composition C" means that the Al content in the powder is 7.0 mass% and the Ca content is 4.7 mass%. "Composition D" means that the Al content in the powder is 9.3 mass% and the Ca content is 0.15 mass%.
[0039] In this experiment, the tap density of the powder produced by the high-speed rotating water jet atomization method was adjusted by sieving. In Figures 4 and 5, the sample with the adjusted tap density of the powder is indicated as "a," and the sample with the unadjusted tap density of the powder is indicated as "b."
[0040] According to step S120 shown in FIG. 2, the chips and the above-mentioned powder were placed in a 1-liter container with a lid and mixed by shaking to obtain the following samples. Sample 1 is composed of only chips. Sample 6 is composed of only powder. Therefore, in the production of Sample 1, only chips were prepared in step S110, and in the production of Sample 6, only powder was prepared in step S110. Furthermore, in the production of Sample 1 and Sample 6, step S120 was omitted. Also, in Samples 2 to 5, the remainder of the powder is composed of chips. For example, since the proportion of powder in Sample 2 is 5% by mass, the proportion of chips in Sample 2 is 95% by mass. <Sample 1> Tips. <Sample 2 to Sample 5> A mixed material obtained by mixing powder having composition A and adjusted tap density with chips. <Sample 6> Powder having composition A and adjusted tap density. <Sample 7 and Sample 8> A mixed material obtained by mixing chips with a powder having composition A and whose tap density has not been adjusted. <Sample 9 to Sample 11> A mixed material obtained by mixing chips with powder having composition B and adjusted tap density. <Sample 12> A mixed material obtained by mixing chips with a powder having composition B whose tap density has not been adjusted. <Sample 13> A mixed material obtained by mixing chips with powder having composition C and adjusted tap density. <Sample 14> A mixed material obtained by mixing chips with a powder having composition C and whose tap density has not been adjusted. <Sample 15> A mixed material obtained by mixing chips with a powder having composition D and adjusted tap density.
[0041] Each sample was subjected to thixomolding to produce a molded product according to the molded product production method shown in Fig. 3. A magnesium injection molding machine JLM75MG manufactured by Japan Steel Works, Ltd. was used to produce the molded product. The slurry temperature was 625°C. The mold temperature was 220°C.
[0042] FIG. 6 is a cross-sectional view showing the cavity 10 of the mold used to manufacture the molded product in this experiment. That is, in this experiment, the molded product was molded into a shape corresponding to the shape of the cavity 10. The cavity 10 has a flat columnar shape with a width W=150 mm, a depth D=50 mm, and a height of 1 to 3 mm. The depth D of the cavity 10 refers to the length in the thickness direction of the paper surface of FIG. 4. The depth D is omitted in FIG. 6. The height of the cavity 10 is configured to be gradually lowered from the third region 13 to the first region 11. Specifically, the first region 11 has a height h1=1 mm, the second region 12 has a height h2=2 mm, and the third region 13 has a height h3=3 mm. The width of each region is all 50 mm. A gate 14 is connected to the third region 13. In the molding process, the slurry is injected into the cavity 10 through the gate 14.
[0043] The tap density of the powder was measured at 100 cm in accordance with JIS Z2512 as described above. 3 The measurement was performed using a measuring container.
[0044] The 0.2% yield strength of the molded product was measured as follows. First, 20 test pieces were prepared by cutting out test pieces of 50 mm width × 10 mm depth × 2 mm height from the second region 12 shown in FIG. 6. Then, a three-point bending test was performed on each test piece with a gauge length of 40 mm. Furthermore, the 0.2% yield strength of the molded product was measured using the results of the three-point bending test.
[0045] As shown in Fig. 4, in Samples 2 to 4, the average value of the yield strength was larger than that of Sample 1, and the difference between the average value and the minimum value of the yield strength was smaller than that of Sample 6 and was approximately the same as that of Sample 1. That is, when the powder ratio was 5 mass% or more and 45 mass%, and the tap density of the powder was 0.15 g / cm 3 The molded products made from the above samples had a higher average yield strength than those made from chips alone, and the difference between the average and minimum yield strength was smaller than that of those made from powder alone, and was comparable to that of those made from chips alone. Powder has a finer structure than chips, so it is presumed that the average yield strength was improved in samples 2 to 4. It is also presumed that the generation of bubbles in the molded products was suppressed in samples 2 to 4, which reduced the difference between the average and minimum yield strength.
[0046] On the other hand, in sample 5, the average value of the yield strength was larger than in sample 1 and sample 6, but no decrease in the difference between the average value and the minimum value of the yield strength was observed. It is presumed that the yield strength was improved in sample 5 because the powder has a finer structure than the chips. On the other hand, it is presumed that the generation of bubbles in the molded product was not effectively suppressed in sample 5 because the proportion of powder contained in the sample was higher than in samples 2 to 4. In addition, in sample 7, the decrease in the difference between the average value and the minimum value of the yield strength was small. Furthermore, in sample 8, a so-called short circuit occurred due to insufficient injection of the material, and the 0.2% yield strength of the molded product could not be measured. It is presumed that the tap density of the powder in samples 7 and 8 is smaller than that of samples 2 to 4, so the generation of bubbles in the molded product was not effectively suppressed.
[0047] As shown in FIG. 5, the average value of the yield strength was improved for Sample 9, Sample 10, and Sample 13, as in Sample 2 to Sample 4, and the difference between the average value of the yield strength and the minimum value was reduced. In Sample 15, the difference between the average value of the yield strength and the minimum value was reduced, as in Sample 2 to Sample 4, but the average value of the yield strength was smaller than that of the other samples represented as "Examples". This is presumed to be because the Ca content in Sample 15 is less than 0.2 mass%. That is, it is preferable that the Ca content in the mixed material is 0.2 mass% or more. On the other hand, since the average value of the yield strength in Sample 15 is about the same as the average value of the yield strength in Sample 1, it is presumed to have a higher yield strength than a chip composed only of chips having a similar composition. In addition, in Sample 11, the proportion of powder contained in the sample is higher than that of the samples represented as "Examples", so the reduction in the difference between the average value of the yield strength and the minimum value was smaller. In Samples 12 and 14, the tap density of the powder contained in the samples was smaller than that of the samples labeled "Examples," and therefore the reduction in the difference between the average and minimum yield strength values was smaller.
[0048] According to the experimental results described above, the ratio of powder in the mixed material is 5 mass% or more and 45 mass% or less, and the tap density of the powder is 0.15 g / cm 3 It was confirmed that when the content of Ca in the powder is 0.2 mass% or more, the variation in strength of the molded product is suppressed. It was also confirmed that the powder preferably contains Ca. It was also confirmed that the content of Ca in the powder is preferably 0.2 mass% or more.
[0049] C. Other forms: The present disclosure is not limited to the above-mentioned embodiment, and can be realized in various forms without departing from the spirit of the present disclosure. For example, the present disclosure can be realized in the following forms. The technical features in the above-mentioned embodiments corresponding to the technical features in each form described below can be appropriately replaced or combined in order to solve some or all of the problems of the present disclosure, or to achieve some or all of the effects of the present disclosure. Furthermore, if the technical feature is not described as essential in this specification, it can be appropriately deleted.
[0050] (1) According to a first aspect of the present disclosure, there is provided a magnesium thixomolding injection molding material. The magnesium thixomolding injection molding material includes a powder containing Mg as a main component and chips containing Mg as a main component. The proportion of the powder in the magnesium thixomolding injection molding material is 5% by mass or more and 45% by mass or less, and the tap density of the powder is 0.15 g / cm. 3 That's all. According to this embodiment, the variation in strength of the molded product is suppressed compared to when a material composed only of powder material is used for thixomolding, and further, the strength of the molded product is improved compared to when a material composed only of chips is used for thixomolding.
[0051] (2) In the magnesium thixomolding injection molding material of the above embodiment, the powder may contain Ca. In this embodiment, the ignition temperature of the powder is increased, so that the magnesium thixomolding injection molding material can be processed more safely and efficiently.
[0052] (3) In the magnesium thixomolding injection molding material of the above embodiment, the Ca content in the powder may be 0.2 mass% or more. With such an embodiment, the ignition temperature of the powder is increased and the strength of the molded product is increased.
[0053] The present disclosure is not limited to the magnesium thixomolding injection molding material described above, and may be realized in various forms, for example, in the form of a molded product containing the magnesium thixomolding injection molding material. [Explanation of symbols]
[0054] Reference Signs List 1... injection molding machine, 2... mold, 5... hopper, 6... heater, 7... heating cylinder, 8... screw, 9... nozzle, 10... cavity, 11... first area, 12... second area, 13... third area, 14... gate
Claims
1. A magnesium thixomolding injection molding material comprising: A powder containing Mg as the highest content of the substance; A chip having a substance with a highest content of Mg among the substances contained therein, The powder content in the magnesium thixomolding injection molding material is 5%. % by mass or more and 45% by mass or less, The tap density of the powder is 0.15 g / cm or more. Magnesium thixomolding injection molding material.
2. 2. The magnesium thixomolding injection molding material according to claim 1, The powder contains Ca, and is a material for magnesium thixomolding injection molding.
3. The magnesium thixomolding injection molding material according to claim 2, The content of Ca in the powder is 0.2 mass% or more. Material for molding injection molding.
Citation Information
Patent Citations
Granular feed material for metal injection molding
JP1996501128A
Production of magnesium alloy molding
JP1998317077A
Raw alloy powder and manufacturing method therefor
JP2005256133A
Raw material for thixotropic molding, method for producing raw material for thixotropic molding, and molded body
JP2019044227A